Navigating modernity: young adults’ perspective on urban transformation in three Lima neighbourhoods - Córdova Ramírez, Miguel (2024)
This article delves into young adults’ perceptions in Lima regarding urban modernization and its relationship with architectural styles and facades. Through semi-structured interviews and visual aids, the study examines how young adults perceive modernity in their urban environment and the discrepancies between their interpretations and conventional notions promoted by developers. Findings reveal a divergence between the envisioned improvements by modernists and the scepticism expressed by young adults, raising questions about the essence of modernization and its implications for Lima. The study underscores the importance of reconciling these discrepancies to ensure urban development aligns with the aspirations of Lima’s residents.